Review of A complete guide to Antarctic wildlife: birds and mammals of the Antarctic Continent and the Southern Ocean, by Hadoram Shirihai - Mehlum, Fridtjof (Polar Research, 2012)
This impressive book is an invaluable, fully illustrated, wildlife guide for tourists and scientists visiting the Southern Ocean and Antarctica.
Keywords: Antarktis; Sørishavet; bokanmeldelser; dyreliv; fugler; marin biologi; ornitologi; pattedyr; zoologi

Culturable heterotrophic bacteria from Potter Cove, Antarctica, and their hydrolytic enzymes production - Tropeano, Mauro; Coria, Silvia; Turjanski, Adrían; Cicero, Daniel; Bercovich, Andrés; Mac Cormack, Walter; Vázquez, Susana (Polar Research, 2012)
Affiliations of the dominant culturable bacteria isolated from Potter Cove, South Shetland Islands, Antarctica, were investigated together with their production of cold-active hydrolytic enzymes. A total of 189 aerobic heterotrophic bacterial isolates were obtained at 4°C and sorted into 63 phylotypes based on their amplified ribosomal DNA restriction analysis profiles. The sequencing of the 16S rRNA genes of representatives from each phylotype showed that the isolates belong to the phyla Proteobacteria (classes Alpha- and Gamma-proteobacteria), Bacteroidetes (class Flavobacteria), Actinobacteria (class Actinobacteria) and Firmicutes (class Bacilli). The predominant culturable group in the site studied belongs to the class Gammaproteobacteria, with 65 isolates affiliated to the genus Pseudoalteromonas and 58 to Psychrobacter. Among the 189 isolates screened, producers of amylases (9.5%), pectinases (22.8%), cellulases (14.8%), CM-cellulases (25.4%), xylanases (20.1%) and proteases (44.4%) were detected. More than 25% of the isolates produced at least one extracellular enzyme, with some of them producing up to six of the tested extracellular enzymatic activities. These results suggest that a high culturable bacterial diversity is present in Potter Cove and that this place represents a promising source of biomolecules. Keywords: Microbial enzymes; Antarctic bacteria; marine bacteria; cold enzymes; psychrophiles.
Keywords: Sørishavet; alger; bakterier; biodiversitet; marin biologi; sjøvann; økologi; økosystemer